Castor cumple cien años - Anne Zelensky (Investigaciones Feministas, 2009)
The centenary of Simone de Beauvoir´s birth is the right moment to release her from the purgatory where she was relegated in France, due to her intellectual stature and her nonconformist complaint against the un observance of one of the principles of the Revolution: gender equality. Beauvoir tries to unveil the world through her own experience. Her good disposition to achieve happiness moved her to the deconstruction of the woman status/nature and to propose an alternative womanhood. Her thought became a valuable base for the political feminism of the ´70s, which found in it a masterful theory.